THE EFFECT OF SHADING ON THE LENGTH OF INCUBATION AND HATCHING SUCCESS OF GREEN TURTLE (Chelonia mydas) EGGS IN PANGUMBAHAN, SUKABUMI, WEST JAVA - Leni, Yusyam; Zamani, Neviaty Putri; Natih, Nyoman Metta Nyanakumara; Bareta, Ainun Rohmawati; Roiska, Riris (Jurnal Perikanan Unram, 2025)
The condition of the nest greatly determines the success of turtle egg hatching. The success of turtle egg hatching, both naturally and artificially, is influenced by several factors such as the location of the nest, the depth of the nest, vegetation conditions, environmental temperature, humidity and the surrounding environment. This study aims to see the effect of shade on the length of the incubation period and the success of green turtle egg hatching in semi-natural nests. This study was conducted at Pangumbahan Nesting Beach, Sukabumi. This study used an experimental method with the treatment of semi-natural nests placed in exposed areas and shaded areas with different depths, namely 68 (control), 30, 50, 70 and 90 cm. Measurements and observations of environmental conditions were carried out during the incubation period. Observations of hatching of hatchlings began on the 55th day of incubation and the dismantling of the entire nest was carried out on the 68th day of incubation. The results showed that in exposed areas there was no significant difference given the level of treatment on the length of the incubation period, while in sheltered or protected areas there was at least one difference in the level of treatment that had a different effect on the length of the incubation period. The fastest incubation period in exposed areas was at a depth of 30 cm and in sheltered areas was at a depth of 90 cm. Key words: incubation period, the green turtle, the success of hatching.